Lumbar disc prolapsed among families in Iraq - Abdulkareem Othman Alrawi, Aymen; Rashied Salih, Mohammed; Abdulmajeed Saeed, Ghadhfan (International Journal of Psychosocial Rehabilitation, 2022)
Intervertebral disc pathology (IVD)including herniation is a common disorder that can be caused by multifactorial genetic, mechanical, behavioral, and environmental, but recent studies have revealed that genetic factors are play the main important role in the predisposition of disc diseases.The objective of work is to study if the family history confirm another risk factor for nerve root pain or lumber disc herniation.A cross-sectional study was carried out at Abu-Graib General Hospital, Baghdad, Iraq during the period between August 2019 till March 2021. The age of those group was between (18-66) years old. By physical examination only patients diagnosed having lumbar disc prolapsed included. We measure BMI of those patients and follow up their family during this period. A total of 276 individuals (110 males, and 166 females) diagnosed with intervertebral disc herniation (IDH). All patients were investigated for demographical data including age, sex, site, level of herniation, and family history. We measured weight, height, and BMI for each patients. Twohundred-seventy-six patients with IDH were enrolled with mean age 40.99±13.65 year. The frequent age groups affected lined between 20 to 60 years. Females were more than males documented with M:F ratio 1:1.5. Most of patients were overweight in 122(44.2%), besides, 95(34.4%) obese participants. One-hundred-twenty-two (44.4%) for both right and left site of lesion. The most common level involved in IDH was lumber 4-5 vertebrae in 197(71.4%). Family history was observed in (152, 55.1%). Mother relative was the most common documented in 57(20.7%). In regression analysis, BMI, site of lesion, level of vertebrae, and family history were significantly differences altering development of IDH (P= 0.01, 0.014, 0.01, 0.004), respectively.Herniated lumbar disc is a disease of middle age, obese, and female gender. There are no site or side specific for herniation. The lumber vertebrae are the most level liable for disc prolapse. The strongest risk factors of development IDH are family history, and BMI, besides, lumber region herniation.